0020 Evaluating Genetic Variation as a Possible Method for Increasing Surveillance and Managing Risk of Developing Obstructive Sleep Apnea. (12th April 2019) - Meyer, Jennifer; Bear, Kimberly; Buwolda, Michael; Sorio, Leo; Regn, Dara; Ford, Caelan; Chapleau, Richard
Abstract: Introduction: Obstructive sleep apnea (OSA) has been increasing within the Air Force, with a slight trend appearing to level off more recently. Untreated, OSA's detrimental effects harm the Airman and jeopardize military operations, placing both human and materiel assets at risk. Current practice within the Air Force sleep standard of care is to evaluate a patient for OSA after appearance of symptoms and after referral from a primary care manager (PCM). When recommending sleep studies, PCMs consider many social, physiological, and environmental risk factors including age, race, obesity, and marital status. As symptoms occur at random, including during flight operations, and that lack of sleep can severely decrease aircrew alertness, we considered options for developing a proactive approach to OSA management, specifically intending to show utility in developing a genetic risk screen to provide PCMs. Methods: We evaluated five genetic markers associated with OSA in civilian populations for confirmation within a military cohort of 34 members. Using minimally invasive cheek swabs and commercially available PCR assays, we were able to rapidly genotype subjects for all markers in less than 2 hours post-collection, at less than $10 per subject. Results: The results of our pilot study suggest that there may be a significant relationship between genetic predisposition and risk of OSA. We found that the diagnosis of OSA showed a significant dependence with three of the five polymorphisms tested. We also found that we could create a genotype score that resulted in accurately predicting 81% of the subjects, with a diagnostic odds ratio of 6.3 and a number needed to misdiagnose of 5.2. Conclusion: Evaluating new military accessions could increase force readiness by identifying indicators of sleep apnea during annual preventive check-ups for aviators and enablers, thereby mitigating the potential detrimental sequelae of sleep apnea. Further studies increasing the subject numbers and controlling for other known risk factors are necessary before determining a tool's utility in aeromedical screening. Support (If Any): Funding was provided by an intramural award to RRC.